Analysis of Hydro Test Pressure Variations on A106 Grade B Carbon Steel Pipe Welded Joints with Welding Repair Method - Riswan E.W. Susanto; Kris Witono; Agus Setiawan; Risno Bayu (Journal of Welding Technology, 2022)
Transportation of oil and gas through oil refinery pipelines is faced with problems, including corrosion problems. Corrosion is a natural phenomenon that occurs in metal materials, where corrosion is a process of material damage due to chemical or electrochemical reactions with its environment. The purpose of this study is the results of the analysis of HydroTest pressure variations on the Welding Joints of Carbon Steel Pipes (carbon steel) A106 Gr.B. In the study did not discuss the occurrence of corrosion and other tests, while the welding process in detail was shown in WPS. This experimental research method uses the Welding Repair Method on welded joints according to the ASME IX, ASME B31.3 standard. The research material is A106 GR carbon steel pipe. B is in the form of a U Tube Seal Deck that has undergone corrosion and damage, where later the fabrication process (pipe repair) especially welding (using SMAW and GTAW) has been determined in PQR and WPS (WPS / CS / EM / ASME / WPxxx). The focus of this research is on stage 9 (hydro testing stage) of the Welding Repair method. Free variables in pressures of 240 Psi, 435 Psi, 690 Psi, and 910 Psi, which have been planned based on the thickness and length of the Pipe joint. Variable fixed temperature test Hydrotest 28OC, holding time holding time (pressurizing) 10 minutes and holding time peak 60 minutes before (depressurizing). The results were obtained that the pressure change was divided into two stages, pressurizing with the highest pressure of 915 Psi is the 4th pressure variation this was obtained from the test observation that there were no leaks in the welded joints and pipe materials in accordance with the acceptance criteria. While the second stage is (depressurizing) with a decrease in pressure or called realese, where successively realese 100%, 75%, 50%, 25%, and 0% at pressures of 915 Psi, 690 Psi, 435 Psi, 240 Psi, 0 Psi with the results of no leakage and observation test results in accordance with the acceptance criteria. So it can be concluded that the welded joints of carbon steel pipes tested using hydrotest, no deformation occurs, there is no change in shape and there are no leaks in the welded joint layer of A106 Gr.B carbon steel pipe